Recurrent RHOA mutations in pediatric Burkitt lymphoma treated according to the NHL-BFM protocols - Rohde, Marius; Richter, Julia; Schlesner, Matthias; Betts, Matthew J.; Claviez, Alexander; Bonn, Bettina R.; Zimmermann, Martin; Damm-Welk, Christine; Russell, Robert B.; Borkhardt, Arndt; Eils, Roland; Höll, Jessica; et al. (Genes, chromosomes & cancer, 2014)
Burkitt lymphoma (BL) is the most frequent B-cell lymphoma in childhood. Genetically, it is characterized by the presence of an IG-MYC translocation which is supposed to be an initiating but not sufficient event in Burkitt lymphomagenesis. In a recent whole-genome sequencing study of four cases, we showed that the gene encoding the ras homolog family member A (RHOA) is recurrently mutated in pediatric BL. Here, we analyzed RHOA by Sanger sequencing in a cohort of 101 pediatric B-cell lymphoma patients treated according to Non-Hodgkin's Lymphoma Berlin-Frankfurt-Münster (NHL-BFM) study protocols. Among the 78 BLs in this series, an additional five had RHOA mutations resulting in a total incidence of 7/82 (8.5%) with c.14G>A (p.R5Q) being present in three cases. Modeling the mutational effect suggests that most of them inactivate the RHOA protein. Thus, deregulation of RHOA by mutation is a recurrent event in Burkitt lymphomagenesis in children.
Gesehen am 08.04.2021